Le pergélisol dans les vallées de la Clarée et de l’Ubaye (Alpes françaises du sud) : un modèle de distribution spatiale établi à partir des températures d’eau de sources et des facteurs topo-climatiques - Romain Perrier; Etienne Cossart; Monique Fort (Cybergeo, 2016)
This study presents the spatial distribution of mountain permafrost based on spring water temperature in two valleys of the French Southern Alps. Spring water temperature was used as a response variable in a logistical regression model, and multiple topo-climatic factors extracted from a DEM were used as predictors. The logistical regression model was statistically significant and used to map the probability of permafrost occurrence.. The results indicate that permafrost lower limit may be located at elevations above 2600 m in favorable settings. This lower limit tends to rise as the incoming solar radiation is increasing. According to the model, the mountain permafrost covers ~2% to 10% of the study area.